Limestone particle size, calcium and phosphorus levels, and phytase effects on live performance and nutrients digestibility of broilers - Majeed, S. (Poult Sci, 2020)
Limestone particle size (PS) affects its solubility and thus can influence broiler performance by altering the rate of calcium (Ca) release into the gastrointestinal tract. The objective of this research was to determine, using 2 × 2 × 2 factorial arrangement, the influence of PS (fine and coarse) and supplemented phytase (0 and 1,000 FYT/kg) in diets formulated with 2 Ca and P(i) levels (positive control [PC]; negative control [NC]) on live performance, bone ash, and apparent ileal nutrients digestibility (AID). Starter PC: 0.9 Ca and 0.45 Pi; NC: 0.72 Ca and 0.03 Pi. Grower PC: 0.76 Ca and 0.38 Pi; NC: 0.58 Ca and 0.23 Pi. The 8 diets were assigned randomly to a total of 1,512 birds, with 21 birds per pen and 9 pens per treatment. The main effects of PS and Ca and P(i) levels had no influence on feed intake (FI), body weight gain (BWG), or feed conversion ratio. Adding phytase improved BWG by 8 g and 50 g and FI by 25 g and 56 g at 0–14 D (P ≤ 0.05) and 0–35 D (P ≤ 0.05), respectively. Interaction between Ca and P(i) levels and phytase improved BWG and FI for 0–14 D (P ≤ 0.05) and BWG during 15–28 D (P ≤ 0.05) for PC without phytase and for PC and NC with phytase when compared with NC without phytase. Birds fed PC without phytase, or either PC or NC with phytase were about 96 g heavier than NC without phytase. Birds fed either PC or NC diet with coarse limestone or PC with fine limestone gained approximately 14 g more (P ≤ 0.05) than birds fed NC with fine limestone for BWG at 0–14 D (P ≤ 0.05). Phytase increased tibia bone ash (14 D) by 1% (P ≤ 0.05). AID of Ca and P(i) at 14 D was improved (P ≤ 0.05) by 66% when phytase was added to coarse limestone. Results indicate that phytase improved broiler performance without being affected by PS. Furthermore, phytase had greater influence on coarse limestone than on fine limestone for bone ash and AID. Ca and P(i) levels were the most influential factors in determining bone ash although phytase inclusion could lead to an improvement during early days.